تقييم مستوى تطبيق الوظائف الأساسية لنظام الحوكمة في إطار نظام الملاءة 2 الأوروبي في شركات التأمين الجزائرية: Evaluation of the level of application of the key functions of the governance system under the European solvency 2 in Algerian insurance companies - سنجاق الدين نور الدين; حساني حسين (Journal of North African Economies, 2025)
The study aims to evaluate the extent to which the key functions of the governance system under European Solvency 2 are implemented in Algerian insurance companies. This is based on the questionnaire and its analysis using the Statistical Package for Social Sciences (SPSS.V26). The study shows that Algerian insurance companies do not adopt an effective risk management function. The compliance function is not adopted as it is a new function. They also adopt an effective framework for the internal audit function, and an acceptable commitment to the actuarial function. The study recommends requiring insurers to adopt a risk management function which put a system that is effective in terms of monitoring and managing risk, giving the actuarial function greater importance and independence. It also recommends the assigning of a responsible in the internal audit function to monitor the insurance company’s compliance with internal regulations and external legislation.